Influence of Cutting Parameters on the Hard Turning of AISI 4140 Steel - Hernández González, Luis Wilfredo; Castillo-Pantoja, Hiovanis; Castillo-Pantoja, Hiovanis; Curra-Sosa, Dagnier Antonio; Curra-Sosa, Dagnier Antonio; Zayas-Figueras, Enrique Ernesto; Zayas-Figueras, Enrique Ernesto; Pérez-Rodríguez, Roberto (Rev. Téc. Fac. Ing. Univ. Zulia, 2024)
The metal cutting process by machining is generally very resource consuming and complex; therefore, the application of hard machining has grown considerably as a suitable alternative since it represents a sustainable technology for this purpose. However, there are some aspects that need to be addressed, especially those related to the performance of this process. Consequently, in this work, the effects of feed rate and cutting speed on cutting temperature and surface roughness during hard turning of AISI 4140 steel have been analyzed, using the Taguchimethodology to optimize the parameters of cutting. Likewise, the models were determined through a multiple regression analysis, studying their suitability with a residual test. Cutting speed and feed rate were statistically significant factors on cutting temperature and surface roughness, respectively. The surface roughness values obtained varied within an acceptable range, allowing the grinding operation to be replaced. The optimum machining parameters for minimizing cutting temperature and surface roughness were the lowest values of feed rate and cutting speed.Keywords: cutting parameters; cutting temperature; hard turning; surface roughness.